Coastal Area Resilience Assessment Study of Kalibuntu to Rob Flood Disaster: Studi Penilaian Tingkat Ketahanan Kawasan Pesisir Kalibuntu Terhadap Bencana Banjir Rob - Wulandari, Ratri; Nuring Hayati, Nunung; Novi Listyawati, Ratih (MATRAPOLIS: Jurnal Perencanaan Wilayah dan Kota, 2025)
Probolinggo Regency is one of cities in Indonesia located on the north coast of Java which has a relatively flat and plain. This condition causes Probolinggo to hava a potential for various disaster risks, one of which is tidal flooding. The three sub-districts that are areas with the highest intensity of tidal flooding are Kraksaan District, Paiton District and Gending District. The coastal area in Kraksaan District, Probolinggo Regency is a lowland with an altitude of 0-100 m above sea level which is prone to tidal flooding. The tidal flood incident in Kraksaan District mostly inundated Kalibuntu Village which is a fishing village and has the highest population density of 7,989 km2 (BPS Probolinggo Regency, 2020). Many community business areas were inundated by tidal flooding such as 496.80 ha of ponds which caused crop failure for pond farmers, community rice fields covering an area of 311.12 ha caused damage to the commodities planted (Pratama et al, 2017). These losses will have a negative impact on the sustainable livelihoods of people living on the coast if tidal floods continue to occur repeatedly. Based on these conditions, it is necessary map disaster vulnerability using 4 vulnerability parameters, namely physical, social, economic and environmental vulnerability. Areas with high vulnerability due to very high population and settlement density can cause the area to be vulnerable to disasters. After the level of vulnerability is known, an assessment of the resilience of the Kalibuntu coastal area to tidal flood disasters will be carried out by several selected respondents using the ANP (Analitycal Network Process) method with the final output is determining priority criteria and selecting the best alternatives that can be used as recommendations for increasing the resilience of Kalibuntu coastal area to tidal flood disasters. The main priority in increasing the resilience of Kalibuntu coastal area is optimizing the improvement of tidal flood mitigation infrastructure.